4 - Implications of Social Media on Student Activism: The South African Experience in a Digital Age - Ntuli, Mthokozisi Emmanuel; Teferra, Damtew (Journal of Higher Education in Africa, 2007)
While the phenomenon of student protest in South Africa is not new, what characterizes the current wave is the successful use of social media to communicate and galvanize students to participate in protests across the country. Recent studies on the use of social media have noted that this form of communication greatly enhances the strength of student movements. However, some scholars have argued that the resulting leadership vacuum, undermines the achievement of their demands and makes it more difficult for the government and higher education authorities to effectively respond to such action. Through the lens of the learning community theory, this article reviews the current literature on social media and student activism in order to establish the effectiveness of its use and the shortcomings thereof. It argues that higher education institutions and the government need to become more conversant with the implications of digital infrastructure. It further suggests that these institutions should create an environment that supports and encourages effective use of social media through provision of the necessary infrastructure. The article provides a deeper understanding of the role that social media can play to galvanize students to advance their causes.